2004
DOI: 10.1111/j.0021-8782.2004.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver error involved in independent attempts to measure cusp base areas of Pan M1s

Abstract: Cusp base areas measured from digitized images increase the amount of detailed quantitative information one can collect from post-canine crown morphology. Although this method is gaining wide usage for taxonomic analyses of extant and extinct hominoids, the techniques for digitizing images and taking measurements differ between researchers. The aim of this study was to investigate interobserver error in order to help assess the reliability of cusp base area measurement within extant and extinct hominoid taxa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 20 publications
2
33
0
3
Order By: Relevance
“…Recently, many dental studies based on image analysis of the occlusal morphology of fossil hominins (e.g., Bailey, 2004;Bailey and Lynch, 2005;Martinan-Torres et al, 2006;Gamez-Robles et al, 2007;Moggi-Cecchi and Boccone, 2007), non human extant primates (e.g., Bailey et al, 2004;Pilbrow, 2006;Hlusko et al, 2007), and recent modern human populations (e.g., Harris and Dinh, 2006;Perez et al, 2006;Bernal, 2007) have been published. Classical morphometric methods applied to image analyses (measurement of diameters and cusp areas) have demonstrated that African robust and non-robust groups differed in their P3 morphology (Wood and Uytterschaut,1987;Suwa et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many dental studies based on image analysis of the occlusal morphology of fossil hominins (e.g., Bailey, 2004;Bailey and Lynch, 2005;Martinan-Torres et al, 2006;Gamez-Robles et al, 2007;Moggi-Cecchi and Boccone, 2007), non human extant primates (e.g., Bailey et al, 2004;Pilbrow, 2006;Hlusko et al, 2007), and recent modern human populations (e.g., Harris and Dinh, 2006;Perez et al, 2006;Bernal, 2007) have been published. Classical morphometric methods applied to image analyses (measurement of diameters and cusp areas) have demonstrated that African robust and non-robust groups differed in their P3 morphology (Wood and Uytterschaut,1987;Suwa et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, computed tomography has offered the possibility of directly measuring three-dimensional objects (Hallgrímsson et al, 2008). The other technique is to take measurements on two-dimensional images after projection of the threedimensional objects (Bailey et al, 2004;Quam and Rak, 2008). This is the case when measurements are made on photographic prints or, as in the present study, on the screen of a digital microscope.…”
mentioning
confidence: 95%
“…An evaluation of the reproducibility (precision) of measurements should therefore be standard in osteometric analyses to detect problematic measurements and to avoid interpretation based on flawed data affected by severe measurement error (Utermohle and Zegura, 1982). Knowing the contribution of measurement error to total variance is also important when data generated by different researchers are combined into a single data set (Bailey et al, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations